Review of the status and challenges associated with increasing influenza vaccination coverage among pregnant women in China - Suizan Zhou; Carolyn M. Greene; Ying Song; Ran Zhang; Lance E. Rodewald; Luzhao Feng; Alexander J. Millman (Human Vaccines & Immunotherapeutics, 2020)
Influenza vaccination coverage in pregnant women in China remains low. In this review, we first provide an overview of the evidence for the use of influenza vaccination during pregnancy. Second, we discuss influenza vaccination policy and barriers to increased seasonal influenza vaccination coverage in pregnant women in China. Third, we provide case studies of successes and challenges of programs for increasing seasonal influenza vaccination in pregnant women from other parts of Asia with lessons learned for China. Finally, we assess opportunities and challenges for increasing influenza vaccination coverage among pregnant women in China.